2016
DOI: 10.5219/579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding milk thistle seed cakes on quality indicators of broiler chickens meat

Abstract: This study was conducted to evaluate the effect of feeding milk thistle (Silybum marianum L.) seed cakes at dose 5% and 15% in feed mixture on quality indicators of broiler chickens meat. The used milk thistle seed cakes contained 3.73% of flavonolignans and 129.83 mg.kg -1 of cyanidin-3-glucoside. A 150 cockerels of Ross 308 were divided into three equal groups. The chickens were fattened on conventional deep litter system. The experimental groups received feed mixtures containing 5% of milk thistle seed cake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The absence of an impact of milk thistle in broiler chicken feed on the total protein content in breast and leg muscles corroborates the results obtained by Št'astník et al [48]. However, own studies showed a significant reduction in the amount of crude fat contained in the leg muscles of birds receiving feed rations with milk thistle in comparison to the control group.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The absence of an impact of milk thistle in broiler chicken feed on the total protein content in breast and leg muscles corroborates the results obtained by Št'astník et al [48]. However, own studies showed a significant reduction in the amount of crude fat contained in the leg muscles of birds receiving feed rations with milk thistle in comparison to the control group.…”
Section: Discussionsupporting
confidence: 88%
“…The studies and experiments carried out by Kralik et al [47] and Št'astník et al [48] showed different impacts of diets containing milk thistle on the acidity of broiler chickens' meat. The results did not corroborate an impact of the nutrition used on the reaction of breast and leg muscles, while Kralik et al [47] found a decrease in the initial pH and an increase in the final pH of breast muscles after adding 3% of oil to the diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, from the fattening point of view, the live weight of chickens decreased where the content of seed cakes in the mixtures increased [ 34 , 46 , 47 , 48 ]. The trend of the lower live weight of chickens with an increasing proportion of expellers was also confirmed in the study of Suchý et al [ 39 ], who found that the addition of 0.2% and 1% milk thistle expellers (2% crude fiber content in diets) led to a statistically insignificant reduction in live weight and feed conversion.…”
Section: The Seed Cakes As a Feedmentioning
confidence: 99%